2021
DOI: 10.1177/15353702211021601
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectric, tissue, and molecular characteristics of the gastric mucosa at different times of ischemia

Abstract: Gastrointestinal ischemia may be presented as a complication associated with late shock detection in patients in critical condition. Prolonged ischemia can cause mucosal integrity to lose its barrier function, triggering alterations that can induce organ dysfunction and lead to death. Electrical impedance spectroscopy has been proposed to identify early alteration in ischemia-induced gastric mucosa in this type of patients. This work analyzed changes in impedance parameters, and tissue and molecular alteration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Subsequently, most focal injuries tend to occur within the interior of the epithelium, where broken blood vessels are more prevalent due to the dysregulation of vascular endothelial cells (ECs), resulting in reduced GMBF, ischaemia, hypoxia and tissue necrosis. Relevant studies have indicated that tissue damage caused by ischemia lasting for more than 60 min induces the loss of barrier function in the GM ( Eduardo, et al, 2021 ). And the damaging agents that accompany with GMBF can reach the lamina propria, causing gastric hydrochloric acid-related disorders mediated by parietal cells that penetrate into the interior of the lamina propria.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, most focal injuries tend to occur within the interior of the epithelium, where broken blood vessels are more prevalent due to the dysregulation of vascular endothelial cells (ECs), resulting in reduced GMBF, ischaemia, hypoxia and tissue necrosis. Relevant studies have indicated that tissue damage caused by ischemia lasting for more than 60 min induces the loss of barrier function in the GM ( Eduardo, et al, 2021 ). And the damaging agents that accompany with GMBF can reach the lamina propria, causing gastric hydrochloric acid-related disorders mediated by parietal cells that penetrate into the interior of the lamina propria.…”
Section: Introductionmentioning
confidence: 99%